Method for preparing high-strength and high-conductivity CuCrZr alloy by using laser powder bed fusion technology

By adding LaB6 powder to the CuCrZr alloy powder and using laser powder bed fusion technology for melt forming, the problem of low strength and conductivity of CuCrZr alloy in the prior art was solved, and a high-strength and high-conductivity CuCrZr alloy preparation was achieved.

CN119710343APending Publication Date: 2025-03-28YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510018415.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Prior art When preparing CuCrZr alloys using laser selection additive manufacturing, it is difficult to simultaneously improve their strength and conductivity.

Method used

By adding LaB6 powder to the CuCrZr alloy powder, melt forming by laser powder bed fusion technology is carried out to achieve in-situ synthesis of CuCrZr/LaB6 alloy.

Benefits of technology

Without post-treatment such as solid solution, aging and heat, a CuCrZr alloy with a yield strength of 242 MPa and a tensile strength of 385 MPa was obtained and had a conductivity of 78.2% ICAS.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710343A_ABST
    Figure CN119710343A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-strength and high-conductivity CuCrZr alloy by using a laser powder bed fusion technology, and belongs to the technical field of additive manufacturing, and the method comprises the following steps: adding LaB6 powder into CuCrZr alloy powder, fully mixing, and drying to obtain mixed alloy powder; and a laser powder bed fusion technology is adopted, the mixed alloy powder is subjected to fusion forming, and in-situ synthesis of the CuCrZr / LaB6 alloy is achieved in the fusion and solidification process. According to the method, a trace amount of LaB6 micron particles are added into the CuCrZr alloy powder, the mixed powder obtained after laser melting and solidification is adopted to achieve in-situ synthesis of the CuCrZr / LaB6 composite material, heterogeneous and double precipitated phase structures are achieved, the printing state CuCrZr alloy strength is greatly improved, and meanwhile good electric conductivity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additive manufacturing, and specifically relates to a method for preparing a high-strength and high-conductivity CuCrZr alloy by using laser powder bed fusion technology. Background Art

[0002] With the rapid development of new energy vehicles and artificial intelligence, the demand for heat dissipation is getting higher and higher, especially for heat dissipation parts with complex shapes, miniaturization and integration.

[0003] CuCrZr alloy is widely used in the field of heat dissipation due to its excellent electrical conductivity, thermal conductivity, high hardness, wear resistance, explosion resistance, crack resistance and high softening temperature. However, due to the difficulties of traditional processing methods in forming complex internal shapes, topological optimization and bionic parts, the rapid development of metal additive manufacturing technology has become an effective means to solve the above problems.

[0004] During the additive manufacturing process, the rapid solidification of the metal induces coarse columnar crystal structure and produces supersaturated solid solution, causing lattice distortion. The above two aspects lead to low strength and conductivity of CuCrZr alloy prepared by laser selective additive manufacturing.

[0005] Therefore, simultaneously improving the strength and electrical conductivity of additively formed copper alloys is a technical problem that needs to be urgently solved in this field. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high-strength and high-conductivity CuCrZr alloy using laser powder bed fusion technology, comprising: LaB6 powder is added to CuCrZr alloy powder, mixed thoroughly, and then dried to obtain a mixed alloy powder; Laser powder bed fusion technology is used to melt the mixed alloy powders, and in-situ synthesis of CuCrZr / LaB6 alloy is achieved during the melting and solidification process.

[0009] As a preferred embodiment of the method of the present invention, the CuCrZr alloy powder is composed of Cr, Zr and Cu, and in terms of the mass percentage of each element, the Cr is 1.5%wt, the Zr is 0.2%, and the balance is Cu to make up 100%.

[0010] As a preferred embodiment of the method of the present invention, the particle size of the CuCrZr alloy powder is in the range of 15 to 53 μm.

[0011] As a preferred embodiment of the method of the present invention, the mass of the LaB6 powder accounts for 1-10% of the mass of the entire mixed powder.

[0012] As a preferred embodiment of the method of the present invention, the particle size range of the LaB6 powder is 2~25μm.

[0013] As a preferred embodiment of the method of the present invention, an inert gas is introduced during the melt forming process to protect against oxidation.

[0014] As a preferred embodiment of the method of the present invention, the inert gas includes argon.

[0015] As a preferred embodiment of the method of the present invention, the laser powder bed fusion process is as follows: laser power 375W, scanning speed 400mm / s, scanning spacing 0.1mm, powder layer thickness 30μm, scanning mode reciprocating mode; After each layer is scanned, an inter-layer scanning strategy of rotating 67° layer by layer is adopted.

[0016] Beneficial effects of the present invention: (1) The advantages of the present invention are that by adding LaB6 powder to CuCrZr powder, a CuCrZr alloy doped with a small amount of LaB6 having a yield strength of 242 MPa and a tensile strength of 385 MPa can be obtained in the printed state without post-treatment such as solid solution, aging and hot isostatic pressing, and the alloy has an electrical conductivity of 78.2% ICAS in the printed state without aging treatment; (2) The process flow of the present invention is simple and has the advantage of less precious elements. On the premise of obtaining high-performance copper alloy heat sinks, the cost is greatly reduced, providing technical support for the large-scale promotion and application of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 This is a schematic diagram of the laser powder bed fusion technology in an embodiment of the present invention.

[0018] Figure 2 4 is a hardness comparison diagram of L-PBF formed CuCrZr alloy in an embodiment of the present invention.

[0019] Figure 3 1 is a comparison chart of the tensile strength of L-PBF formed CuCrZr alloy in an embodiment of the present invention.

[0020] Figure 4 4 is a comparison diagram of the electrical conductivity of L-PBF formed CuCrZr alloy in an embodiment of the present invention. DETAILED DESCRIPTION

[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0022] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0023] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0024] The present invention proposes a novel design strategy to produce printed CuCrZr samples with excellent high strength and high conductivity by adding trace amounts of LaB6 nanoparticles; the dispersed nanoprecipitates and heterogeneous microstructures significantly improve the strength and conductivity of the printed CuCrZr alloy without the need for heat treatment.

[0025] The method of the present invention provides a simple and feasible design strategy, which reduces defects such as pores and unmelted parts in printed parts, while enhancing the strength and conductivity of printed CuCrZr alloys, and provides more options for improving the performance of other alloy systems.

[0026] Example 1 The main steps are as follows: (1) The powder of the embodiment is CuCrZr alloy powder with LaB6 powder added thereto, wherein the element ratio of the CuCrZr alloy powder is: Zr: 0.2wt%, Cr: 1.5wt%, and the balance is Cu; The particle size range of CuCrZr alloy powder is: 15~53μm, and the particle size range of LaB6 powder is: 2~25μm; the mass of the added LaB6 powder accounts for 1% of the mass of the whole powder after mixing; Use a drum mixer to mix the powder evenly, set the machine speed to 200r / min, and set the mixing time to 2h.

[0027] (2) Place the mixed CuCrZr+LaB6 alloy powder in a vacuum drying oven at 80°C and dry for 2 hours to prevent the powder from agglomerating due to moisture.

[0028] (3) Use solidworks to design a 3D model and save it as an stl file. Use slicing software to slice the model and save it as an xli file. Then use the filling software to set the laser parameters, printing strategy and model placement; The specific process parameters are as follows: laser power 375W, scanning speed 400mm / s, scanning spacing 0.1mm, powder layer thickness 30μm; The scanning method is reciprocating, and each layer is rotated 67° after scanning.

[0029] (4) Pour the powder into the L-PBF equipment. Wipe the 316 stainless steel substrate and copper plate with alcohol before printing. Use a scraper to flatten the first layer of powder until the substrate is barely visible. Turn on the substrate preheating, set the temperature to 120°C, and introduce argon gas to make the oxygen content in the forming chamber reach 0.1% or less.

[0030] (5) After printing is completed, an electric spark wire cutting machine is used to separate the sample from the substrate. No heat treatment is required. Only an ultrasonic vibrator is used for surface treatment to remove surface powder. Finally, a multi-functional stretching machine and a resistance meter are used to test the hardness, tensile strength and conductivity of the sample.

[0031] Hardness results correspond to Figure 2 1#, the stretching result corresponds to Figure 3 1.0LaB6-CuCrZr-1, conductivity test corresponds to Figure 4 Middle 1#.

[0032] (6) The test method is as follows: The Vickers hardness of the CuCrZr samples was measured using a digital microhardness tester (Taiming-HXD-1000TM / LCD, China) with a step size of 90 μm. Uniaxial tensile tests were performed on a universal tensile machine (Shimadzu AGS-X, Japan) at room temperature and a strain rate of 9 mm / min. The tensile samples were sheared into a dog-bone shape with dimensions of 15 × 3 × 2 mm. 3 The constant loading speed was 9 mm / min, and the fracture morphology was observed in a scanning electron microscope.

[0033] The conductivity of the CuCrZr and 1.0LaB6-CuCrZr samples was measured by a DC resistance tester (HG2511, China). The size of the test sample was 30×2×2 mm 3 The resistivity test of each sample was measured five times to ensure repeatability, and the average value was recorded. The International Annealed Copper Standard (%IACS) identifies the conductivity through formula (1), which is as follows: in, is the resistivity (Ωmm), δ is IACS, 0.01724 is the resistivity of pure copper after annealing, and the other embodiments and comparative examples adopt the same testing method, which is omitted later.

[0034] See the schematic diagram of the laser powder bed fusion technology in this embodiment. Figure 1 .

[0035] Example 2 The main steps are as follows: (1) The powder of the embodiment is CuCrZr alloy powder with LaB6 powder added thereto, wherein the element ratio of the CuCrZr alloy powder is: Zr: 0.2wt%, Cr: 1.5wt%, and the balance is Cu; The particle size range of CuCrZr alloy powder is: 15~53μm, and the particle size range of LaB6 powder is: 2~25μm; the mass of the added LaB6 powder accounts for 1% of the mass of the whole powder after mixing; Use a drum mixer to mix the powder evenly, set the machine speed to 200r / min, and set the mixing time to 2h.

[0036] (2) Place the mixed CuCrZr+LaB6 alloy powder in a vacuum drying oven at 80°C and dry for 2 hours to prevent the powder from agglomerating due to moisture.

[0037] (3) Use solidworks to design a 3D model and save it as an stl file. Use slicing software to slice the model and save it as an xli file. Then use the filling software to set the laser parameters, printing strategy and model placement; The specific process parameters are as follows: laser power 350W, scanning speed 500mm / s, scanning spacing 0.1mm, powder layer thickness 30μm; The scanning method is reciprocating, and each layer is rotated 67° after scanning.

[0038] (4) Pour the powder into the L-PBF equipment. Wipe the 316 stainless steel substrate and copper plate with alcohol before printing. Use a scraper to flatten the first layer of powder until the substrate is barely visible. Turn on the substrate preheating, set the temperature to 120°C, and introduce argon gas to make the oxygen content in the forming chamber reach 0.1% or less.

[0039] (5) After printing, the sample is separated from the substrate using an EDM wire cutting machine. No heat treatment is required. Only an ultrasonic vibrator is used for surface treatment to remove surface powder. Finally, a multifunctional tensile machine and a resistance meter are used to test the hardness, tensile strength and conductivity of the sample. The hardness results correspond to Figure 2 2#, the stretching result corresponds to Figure 3 1.0LaB6-CuCrZr-2, conductivity test corresponds to Figure 4 Middle 2#.

[0040] Example 3 The main steps are as follows: (1) The powder of the embodiment is CuCrZr alloy powder with LaB6 powder added thereto, wherein the element ratio of the CuCrZr alloy powder is: Zr: 0.2wt%, Cr: 1.5wt%, and the balance is Cu; The particle size range of CuCrZr alloy powder is: 15~53μm, and the particle size range of LaB6 powder is: 2~25μm; the mass of the added LaB6 powder accounts for 1% of the mass of the whole powder after mixing; Use a drum mixer to mix the powder evenly, set the machine speed to 200r / min, and set the mixing time to 2h.

[0041] (2) Place the mixed CuCrZr+LaB6 alloy powder in a vacuum drying oven at 80°C and dry for 2 hours to prevent the powder from agglomerating due to moisture.

[0042] (3) Use solidworks to design a 3D model and save it as an stl file. Use slicing software to slice the model and save it as an xli file. Then use the filling software to set the laser parameters, printing strategy and model placement; The specific process parameters are as follows: laser power 350W, scanning speed 400mm / s, scanning spacing 0.1mm, powder layer thickness 30μm; The scanning method is reciprocating, and each layer is rotated 67° after scanning.

[0043] (4) Pour the powder into the L-PBF equipment. Wipe the 316 stainless steel substrate and copper plate with alcohol before printing. Use a scraper to flatten the first layer of powder until the substrate is barely visible. Turn on the substrate preheating, set the temperature to 120°C, and introduce argon gas to make the oxygen content in the forming chamber reach 0.1% or less.

[0044] (5) After printing, the sample is separated from the substrate using an EDM wire cutting machine. No heat treatment is required. Only an ultrasonic vibrator is used for surface treatment to remove surface powder. Finally, a multifunctional tensile machine and a resistance meter are used to test the hardness, tensile strength and conductivity of the sample. The hardness results correspond to Figure 2 3#, the stretching result corresponds to Figure 3 1.0LaB6-CuCrZr-3, conductivity test corresponds to Figure 4 Middle 3#.

[0045] Comparative Example 1 The main steps are as follows: (1) The powder of the embodiment is a CuCrZr alloy powder, wherein the element ratio of the CuCrZr alloy powder is: Zr: 0.2wt%, Cr: 1.5wt%, and the balance is Cu.

[0046] (2) Place the CuCrZr alloy powder in a vacuum drying oven at 80°C and dry for 2 hours to prevent the powder from agglomerating due to moisture.

[0047] (3) Use solidworks to design a 3D model and save it as an stl file. Use slicing software to slice the model and save it as an xli file. Then use the filling software to set the laser parameters, printing strategy and model placement. The specific process parameters are as follows: laser power 375W, scanning speed 400mm / s, scanning spacing 0.1mm, powder layer thickness 30μm. The scanning method is reciprocating, and each layer is rotated 67° after scanning.

[0048] (4) Pour the powder into the L-PBF equipment. Wipe the 316 stainless steel substrate and copper plate with alcohol before printing. Use a scraper to flatten the first layer of powder until the substrate is barely visible. Turn on the substrate preheating, set the temperature to 120°C, and introduce argon gas to make the oxygen content in the forming chamber reach 0.1% or less.

[0049] (5) After printing, use an EDM wire cutting machine to separate the sample from the substrate. No heat treatment is required. Only an ultrasonic vibrator is used for surface treatment to remove surface powder. Finally, a multi-function tensile machine and a resistance meter are used to test the hardness, tensile strength and conductivity of the sample. The hardness results correspond to Figure 2 1#, the stretching result corresponds to Figure 3 CuCrZr-1, conductivity test corresponds to Figure 4 Middle 1#.

[0050] Comparative Example 2 The main steps are as follows: (1) The powder of the embodiment is a CuCrZr alloy powder, wherein the element ratio of the CuCrZr alloy powder is: Zr: 0.2wt%, Cr: 1.5wt%, and the balance is Cu.

[0051] (2) Place the CuCrZr alloy powder in a vacuum drying oven at 80°C and dry for 2 hours to prevent the powder from agglomerating due to moisture.

[0052] (3) Use solidworks to design a 3D model and save it as an STL file. Use slicing software to slice the model and save it as an XLI file. Then use the filling software to set the laser parameters, printing strategy and model placement. The specific process parameters are as follows: laser power 350W, scanning speed 500mm / s, scanning spacing 0.1mm, powder layer thickness 30μm. The scanning method is reciprocating, and each layer is rotated 67° after scanning.

[0053] (4) Pour the powder into the L-PBF equipment. Wipe the 316 stainless steel substrate and copper plate with alcohol before printing. Use a scraper to flatten the first layer of powder until the substrate is barely visible. Turn on the substrate preheating, set the temperature to 120°C, and introduce argon gas to make the oxygen content in the forming chamber reach 0.1% or less.

[0054] (5) After printing, use an EDM wire cutting machine to separate the sample from the substrate. No heat treatment is required. Only an ultrasonic vibrator is used for surface treatment to remove surface powder. Finally, a multi-function tensile machine and a resistance meter are used to test the hardness, tensile strength and conductivity of the sample. The hardness result corresponds to Figure 2 2#, the stretching result corresponds to Figure 3 CuCrZr-2, conductivity test corresponds to Figure 4 Middle 2#.

[0055] Comparative Example 3 (1) The powder of the embodiment is a CuCrZr alloy powder, wherein the element ratio of the CuCrZr alloy powder is: Zr: 0.2wt%, Cr: 1.5wt%, and the balance is Cu.

[0056] (2) Place the CuCrZr alloy powder in a vacuum drying oven at 80°C and dry for 2 hours to prevent the powder from agglomerating due to moisture.

[0057] (3) Use solidworks to design a 3D model and save it as an STL file. Use slicing software to slice the model and save it as an XLI file. Then use the filling software to set the laser parameters, printing strategy and model placement. The specific process parameters are as follows: laser power 350W, scanning speed 400mm / s, scanning spacing 0.1mm, powder layer thickness 30μm. The scanning method is reciprocating, and each layer is rotated 67° after scanning. (4) Pour the powder into the L-PBF equipment. Wipe the 316 stainless steel substrate and copper plate with alcohol before printing. Use a scraper to flatten the first layer of powder until the substrate is barely visible. Turn on the substrate preheating, set the temperature to 120°C, and introduce argon gas to make the oxygen content in the forming chamber reach 0.1% or less.

[0058] (5) After printing, use an EDM wire cutting machine to separate the sample from the substrate. No heat treatment is required. Only an ultrasonic vibrator is used for surface treatment to remove surface powder. Finally, a multi-function tensile machine and a resistance meter are used to test the hardness, tensile strength and conductivity of the sample. The hardness result corresponds to Figure 2 1#, the stretching result corresponds to Figure 3 CuCrZr-3, conductivity test corresponds to Figure 4 Middle 3#.

[0059] The present invention adds a trace amount of LaB6 powder to ordinary CuCrZr powder, thereby improving the mechanical properties and physical properties of the printed alloy at the same time, and the performance indicators reach the leading level of the same alloys.

[0060] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a high-strength and high-conductivity CuCrZr alloy using laser powder bed fusion technology, characterized in that: include, LaB6 powder is added to CuCrZr alloy powder, mixed thoroughly, and then dried to obtain a mixed alloy powder; Laser powder bed fusion technology is used to melt the mixed alloy powders, and in-situ synthesis of CuCrZr / LaB6 alloy is achieved during the melting and solidification process.

2. The method according to claim 1, characterized in that: The CuCrZr alloy powder is composed of Cr, Zr and Cu. In terms of the mass percentage of each element, the Cr is 1.5%wt, the Zr is 0.2%, and the balance is Cu to make up 100%.

3. The method according to claim 1 or 2, characterized in that: The particle size of the CuCrZr alloy powder is in the range of 15 to 53 μm.

4. The method according to claim 1, characterized in that: The mass of the LaB6 powder accounts for 1-10% of the mass of the entire mixed powder.

5. The method according to claim 1 or 4, characterized in that: The particle size range of the LaB6 powder is 2-25 μm.

6. The method according to claim 5, characterized in that: In the process of melt forming, an inert gas is introduced to protect and prevent oxidation.

7. The method according to claim 6, characterized in that: The inert gas includes argon.

8. The method according to claim 1 or 7, characterized in that: The process of laser powder bed fusion is as follows: laser power 375W, scanning speed 400mm / s, scanning spacing 0.1mm, powder layer thickness 30μm, and reciprocating scanning mode; After each layer is scanned, an inter-layer scanning strategy of rotating 67° layer by layer is adopted.